2021
DOI: 10.1002/anie.202016051
|View full text |Cite
|
Sign up to set email alerts
|

Direct α‐Tertiary Alkylations of Ketones in a Combined Copper–Organocatalyst System

Abstract: Herein, we report an efficient method for the tertiary alkylation of a ketone by using an α‐bromocarbonyl compound as the tertiary alkyl source in a combined Cu‐organocatalyst system. This dual catalyst system enables the addition of a tertiary alkyl radical to an enamine. Mechanistic studies revealed that the catalytically generated enamine is a key intermediate in the catalytic cycle. The developed method can be used to synthesize substituted 1,4‐dicarbonyl compounds containing quaternary carbons bearing var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…All products were separated by silica gel (200−300 mesh) column chromatography with petroleum ether (PE) (60−90 °C) and ethyl acetate (EA). 1 H, 13 C, and 19 F NMR spectra were recorded on a Bruker Advance 500 spectrometer at ambient temperature with CDCl 3 or CD 3 SOCD 3 as the solvent and tetramethylsilane as the internal standard. Melting points were determined on an X-5 Data microscopic melting point apparatus.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…All products were separated by silica gel (200−300 mesh) column chromatography with petroleum ether (PE) (60−90 °C) and ethyl acetate (EA). 1 H, 13 C, and 19 F NMR spectra were recorded on a Bruker Advance 500 spectrometer at ambient temperature with CDCl 3 or CD 3 SOCD 3 as the solvent and tetramethylsilane as the internal standard. Melting points were determined on an X-5 Data microscopic melting point apparatus.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…19 Later, Nishikata and co-workers developed an efficient copperorganocatalyst system for the C−H alkylation of ketones (Scheme 1a, middle). 13 In the same year, Wu et al demonstrated a palladium-catalyzed denitrative α-arylation of ketones with nitroarenes (Scheme 1a, bottom). 14 Despite their utilities, most of these methods generally suffer from disadvantages such as toxicity associated with metal catalysts and promoters, stoichiometric amounts of oxidants or additives, air and moisture sensitivity, and harsh reaction conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we successfully controlled enamine reactivity during the α-tertiary alkylations of ketones using αbromoesters as tertiary alkyl radical sources to produce acyclic 1,4-dicarbonyl compounds; [23] however, iminium ions did not participate in this CÀ C bond-forming process. Based on these previous reports, we envisaged the following multicyclization strategy that uses α-bromocarboxamides [24] (1) bearing nucleophilic moieties (4; Scheme 1): A tertiary alkyl radical species adds to the enamine to form A, which is subsequently oxidized with Cu II to produce iminium I (B) that undergoes the first cyclization to generate γ-lactam ring C. The resulting γ-lactam intermediate C generates the N-acyl iminium ion D (iminium II), [25] which eliminates a proton to produce 3 or undergoes a second cyclization to generate multiheterocycle 5.…”
Section: Introductionmentioning
confidence: 99%